2009
DOI: 10.1007/s00280-009-0980-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of biweekly gemcitabine followed by oxaliplatin and simplified 48-h infusion of 5-fluorouracil/leucovorin (GOFL) in advanced pancreatic cancer

Abstract: The triplet regimen is feasible and exhibits promising activity against APC, deserving further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Baseline characteristics before starting nal-IRI + 5-FU/ LV were Eastern Cooperative Oncology Group performance score (ECOG PS) 0-1 in 32 (72.7%), presence of metastatic diseases in 39 (88.6%) with 56.8% exhibiting liver metastasis and failed to one prior chemotherapy in 32 (72.7%). The most common prior regimen was gemcitabine-based triplet therapy consisting of gemcitabine, oxaliplatin plus either 5-FU/LV or S-1/LV 14,15 in 24 (54.5%); while only 4 patients (9.1%) had prior exposure to irinotecan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline characteristics before starting nal-IRI + 5-FU/ LV were Eastern Cooperative Oncology Group performance score (ECOG PS) 0-1 in 32 (72.7%), presence of metastatic diseases in 39 (88.6%) with 56.8% exhibiting liver metastasis and failed to one prior chemotherapy in 32 (72.7%). The most common prior regimen was gemcitabine-based triplet therapy consisting of gemcitabine, oxaliplatin plus either 5-FU/LV or S-1/LV 14,15 in 24 (54.5%); while only 4 patients (9.1%) had prior exposure to irinotecan.…”
Section: Resultsmentioning
confidence: 99%
“…For its favorable safety profile, S-1 either alone or combining with gemcitabine are acceptable regimens for less fit, advanced PDAC patients in Japan 10,13 and for all comers in clinical practice before the reimbursement of FOLFIRINOX and the nab-paclitaxel in Taiwan. While biweekly triplet chemotherapy consisting of gemcitabine, oxaliplatin plus either infusion 5-FU/LV (the GOFL regimen) or oral S-1/LV (the SLOG regimen) that have been developed through a series of multicenter trials under the platform of Taiwan Cooperative Oncology Group (TCOG) are the favorable regimens in our institutional clinical practice 14,15 . In a single arm phase II trial, SLOG had 40.7% of overall response rate, and 7.6 and 11.4 months of median progression-free survival and overall survival, respectively, that are comparable with those achievable with FOLFIRINOX in ACCORD 11/0402 study 15 .…”
mentioning
confidence: 99%
“…In a randomized study comparing gemcitabine alone to gemcitabine combined with oxaliplatin, the group receiving the combination had a significantly better RR (26.8 vs. 17.3%, p = 0.04), progression-free survival (5.8 vs. 3.7 months, p = 0.04) and clinical benefit (38.2 vs. 26.9%, p = 0.03), but not OS benefit (9.0 vs. 7.1 months, p = 0.13) [17]. Although the RR of GOFL-treated patients with pancreatic cancer seems very promising [18], the current, still very limited, data do not indicate whether combining other drugs with gemcitabine can actually improve the outcome of this group [19]. However, a recent randomized trial demonstrated that metastatic pancreatic cancer patients receiving FOLFIRINOX (oxaliplatin, irinotecan and 5-FU) have a better RR, progression-free survival and OS than those receiving gemcitabine alone, indicating that a gemcitabine-based combination therapy may offer hope to this group of patients with a bleak prognosis [20].…”
Section: Discussionmentioning
confidence: 99%
“…The results of multiple recent phase II studies provide some support for the 3 drug concept as combinations of gemcitabine, 5FU/capecitabine, and either oxaliplatin or docetaxel yielded response rates ranging from 33% to 41%, on par with FOLFIRNOX and clearly better than the 2 drug regimens 4749 . However, the reported median OS between 7.8 and 9 months in these studies is worse than with FOLFIRINOX, despite a mixed population with 20–40% patients with locally advanced disease.…”
Section: Phase II Clinical Trials In Advanced Pancreatic Cancermentioning
confidence: 95%